Peningkatan Keterampilan Motorik Kasar melalui Permainan Rintangan Sederhana dalam Mengembangkan Kecerdasan Kinestetik Anak Usia 5-6 tahun - Ria Handayani Hasibuan; Febby Ardera Br Ginting; Miftahul Zannah; Mutiara Firdausi An Tasya; Najwa Mawaddah; Fauziah Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
At preschool age, the development of kinesthetic intelligence is strongly influenced by stimulation provided through varied physical activities and games. One approach that can be used by teachers is through games, especially obstacle games or handicap games. These games are designed to provide structured physical challenges, so that children are encouraged to develop gross motor skills, balance, agility, and overall body coordination. This study aims to determine the improvement of grossmotor skills through simple obstacle games. This research is a Classroom Action Research (PTK). The subjects in this study were children in the age range of 5-6 Years at ABA Bustanul 10 Medan Kindergarten ,namely 10 people .Datacollection was done by observation and non-test. This observation is used to determine the ability ofstudents in gross motor skills, the data is analyzed by the percentage formula. The result soft here searc hobtain edwere BB 30%, MB 40%,BSH 20%,BSB 10%.IncycleI and in cycle II BB 0%, MB 20%, BSH 20%, BSB 60%. Gross motor skills in developing kinesthetic intelligence of children aged 5-6 years through simple obstacle games in cycle I only reached completeness with a value of 10% (Less), and in cycle II it increased classically with a value of 60% (Very good). Thus the improvement of gross motor skills of children aged 5-6 years through simple obstacle games can improve gross motor skills in developing kinesthetic intelligence of children aged 5-6 years.